Casos clínicos incomuns e perfil do uso de antibióticos em pequenos animais: estudo retrospectivo (2015-2019) - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The aim of this dissertation was to perform a retrospective study of clinical cases and surgery procedures performed in dogs and cats in university hospital between January 1, 2015 and December 31, 2019. In order to carry out this long study, 3869 clinical and surgical care records were carried out in dogs and cats. In a first step, was carried out the search and identification of passive cases of scientific publication, which resulted in two manuscripts entitled “Severe serotonin syndrome induced for the association of selegiline and sertraline in a dog” and “Intra-abdominal torsion of a non-neoplastic cryptorchid testis in an adult dog”. In the second stage, 1227 small animal surgical clinic files were identified and a quantitative analysis of the antibiotics used in 1053 dogs and cats undergoing surgical procedures was performed. This study was developed in a manuscript “Retrospective study of the use of antibiotics in small animal surgery (2015-2019)”.The first two manuscripts contribute to academic training and research in veterinary medicine. The study of the use of antibiotics in veterinary medicine is of great importance for unique health, as it is directly related to the increase in the number of antibiotic-resistant bacteria. Therefore, knowing the magnitude of antibiotic administration in a Veterinary Hospital is essential to alert professionals about care for their rational use and optimization of their use.
Uncommon clinical cases and profile of antibiotic use in small animals: retrospective study (2015-2019)
Keywords: Antibiotic; Surgery; Serotonin Syndrome; Testicular torsion; Antibiótico; Cirurgia; Síndrome serotonina; Torção testicular; CNPQ::CIENCIAS AGRARIAS